EVALUATING THE EFL CONTEXT TEXTBOOKS IN THE IMPLEMENTATION OF THE 2013 CURRICULUM IN INDONESIA - Manalu, Anastasia Irna Sumiadi (2017)
In this study, the first grade English textbooks in Senior High school were evaluated based on the content development criteria developed by Cunningsworth and criteria of the 2013 Curriculum suggested by Kemendikbud. The analyzed textbooks are entitled "Bahasa Inggris untuk SMA/ MA/ SMK kelas X, one for semester 1 and the other one is for semester 2. This is a qualitative research, focusing on content analysis. The results of the study show that in terms of both criteria, overall, the textbooks have fulfilled the criteria for textbook content development, covering in language skills (listening, speaking, reading, and writing) and the requirements of Curriculum 2013 for English textbook designed for Senior High school students. However, at certain points in the tasks/ activities, the books needs to be improved for these reasons (1) some activities in each chapter are often repetitive, (2) other supplementary material for listening activities are not available and (3) writing and listening activities are considered limited 4) the learning steps in terms of the scientific approach analysis need to be presented in the order as the scientific approach suggested.;---Dalam penelitian ini, buku pelajaran Bahasa Inggris untuk kelas X SMA dievaluasi dengan menggunakan kriteria pengembangan isi dari teori Cunningworth dan kriteria yang disusun dalam Kurikulum 2013 oleh Kemendikbud. Buku tersebut berjudul "Bahasa Inggris untuk SMA/ MA/ SMK kelas X, yang terdiri dari dua buku: satu untuk semester 1 dan lainnya untuk semester 2. Penelitian ini adalah penelitian kualitatif, berfokus pada konten analisis. Hasil penelitian ini menunjukkan bahwa dalam dua kriteria utama buku pelajaran yang digunakan telah memenuhi kriteia pengembangan isi yang mencakup skill berbahasa seperti listening, speaking, reading, and writing), dan sesuai dengan kriteria yang diwajibkan oleh Kurikulum 2013. Hanya saja, ada beberapa hal yang perlu dicatat sebagai bahan perbaikan: (1) beberapa kegiatan teralu sering berulang, (2) materi pelengkap untuk kegiatan listening tidak tersedia, (3) kegiatan writing dan listening terlalu sedikit dan terbatas, (4) langkah-langkah pembelajaran dalam analisis Pendekatan Saintifik perlu disusun sebagaiman yang disarankan oleh Pendektan Saintifik tersebut.